Eosinophilic Solid and Cystic Renal Cell Carcinoma with Non-typical Immunophenotype: A Series of Two Cases. (9th November 2022) - Chen, J; Harbert, J; Bhalla, R; Dewenter, T
Abstract: Introduction/Objective: Eosinophilic solid and cystic renal cell carcinoma (ESC RCC) is an emerging entity receiving increasing attention. Initially characterized in a large series by Trpkov et al, the distinct features of this tumor are voluminous eosinophilic cytoplasm with granular cytoplasmic stippling, mixed solid and cystic architecture, and CK20 positivity/CK7 negativity. Methods/Case Report: We present two cases of ESC RCC diagnosed at our institution which exhibit a non-typical immunophenotype. The patients were a 58-year-old female and a 59-year-old male, with a 5.5 cm and 3.5 cm incidental renal mass, respectively. Both underwent uncomplicated partial nephrectomies. The tumors exhibited solid, alveolar, tubular and focally cystic growth patterns and were composed of cells with voluminous granular eosinophilic cytoplasm. Tubules and cysts were lined by single hobnail layer of neoplastic cells. Characteristic cytoplasmic stippling and compact leishmaniasis-like globules were present. The tumor nuclei were enlarged, with irregular nuclear contours and scattered multinucleation. The second case was significant for a diffuse neutrophil infiltration along with foamy macrophages. Immunohistochemically, the tumor cells were positive for PAX8, AMACR, CD10 and vimentin, while being negative for pan-cytokeratin, CD117, CAIX, Melan A, and HMB45. Interestingly, CK20 was only positive in very rare single cells and CK7 was focally positive in both cases. In our differentials, we considered SDH-deficient, low-grade FH-deficient, and MiT family translocation-associated RCC. FISH studies showed that the tumor cells have retained the expression of FH and SDHB, without TFE3 and TFEB alterations. Although our cases demonstrated non- typical CK20/CK7 expressions, based on the morphology with other molecular manifestations, the diagnosis of ESC RCC was rendered. Results (if a Case Study enter NA): NA. Conclusion: ESC RCC poses diagnostic difficulties as many eosinophilic/oncocytic entities are included in the differentials, and the immunoprofile of this entity is variable. It is important to appreciate the characteristic histomorphologic features to increase its recognition as inclusion into the WHO classification system is likely.